Richard Shusterman vs. uniwersalizm hermeneutyczny - Małecki, Wojciech (Er(r)go. Teoria - Literatura - Kultura, 2006)
Wojciech Małecki Richard Shusterman vs. Hermeneutic Universalism. Inspired by Nietzsche's claim on the superiority of interpretation, the paper explores Shusterman's account of hermeneutic universalism and in a critical manner explores Shusterman's views advocating functional distinction between understanding and interpretation. The polemics revolves around Stanley Fish's theory which, as the Author suggests, Shusterman seems to be at least in a partial agreement with, since (somehow contrary to some of his own views) remains established by the common ground of both Fish's and Shusterman's anti-fundationalist perspective.